Scientific Paradigms in Managerial Decision-Making: Enhancing Strategic Accuracy in Maritime Leadership - Martinus Siagian; Mohamad Iqbal. F.; Mohhamad Ezra P.; Muhammad Verrell C.P.; Nadifa Salsabila H.; Nira L. C. S. (Harmony Management: International Journal of Management Science and Business, 2025)
The maritime industry operates in a complex, rapidly evolving global environment where decision-making accuracy is critical for operational efficiency, sustainability, and risk mitigation. Traditionally, maritime leadership has relied heavily on experience-based decision-making, often leading to cognitive biases and strategic inefficiencies. This study examines the role of scientific paradigms in managerial decision-making, emphasizing how structured epistemological reasoning enhances strategic accuracy and reduces decision-making errors. This research provides original value by addressing the limited integration of structured decision-making models in maritime leadership, which has been largely overlooked in previous studies. While scientific reasoning has transformed decision-making in industries such as finance and healthcare, its application in maritime management remains underdeveloped. The study explores the following research questions: To what extent do scientific paradigms influence managerial decision-making in maritime leadership? How can structured reasoning reduce bias and improve decision accuracy? Using a qualitative approach, semi-structured interviews were conducted with maritime experts, lecturers, and postgraduate students, followed by thematic analysis and comparative evaluation. Results indicate that structured decision frameworks significantly improve managerial effectiveness, yet barriers such as industry conservatism and limited competency development hinder widespread adoption. The study concludes that integrating scientific reasoning into maritime leadership training programs can enhance decision accuracy, promote evidence-based management, and ensure sustainable strategic planning.